Answer:
Option B is correct.
add 4 times the second equation to 3 times the first equation
Explanation:
Given the system of equation:
......[1]
.....[2]
Multiply equation [1] by 3 we get;
![3(2x-4y) = 3 \cdot 6](https://img.qammunity.org/2019/formulas/mathematics/high-school/4j717ti7340w5vlvakvyw6qykxb8hvfybh.png)
Using distributive property;
![a\cdot (b+c) = a\cdot b+ a\cdot c](https://img.qammunity.org/2019/formulas/mathematics/high-school/cttimudjr6bs5xw12b4a4d7r7qp3korqed.png)
6x - 12y = 18 .......[3]
Multiply equation [2] by 4 we get;
![4(-3x+3y) = 4 \cdot 12](https://img.qammunity.org/2019/formulas/mathematics/high-school/7wzoby518czvz0tw6wy10z4t0hyvhbod38.png)
Using distributive property we get;
-12x + 12y = 48 ......[4]
Add equation [3] and [4] to eliminate y and solve for x;
(6x -12y) + ( -12x +12y ) = 18 + 48
6x - 12y -12x + 12y = 66
Combine like terms;
6x - 12x = 66
or
-6x = 66
Simplify:
x = -11
Therefore, the operation which could be used to eliminate the y-variable and find the value of x is;
add 4 times the second equation to 3 times the first equation.